EXPLORING FORGOTTEN LANGUAGES AND THEIR CULTURAL SIGNIFICANCE - Komilova Hilola (Web of Journals Publishing, 2025)
This article delves into the importance of forgotten languages in preserving cultural heritage and the challenges faced due to their decline. It provides an in-depth analysis of the historical, social, and linguistic aspects of these languages, along with efforts being made for their revitalization.
Keywords: Forgotten languages, cultural heritage, language preservation, linguistic diversity, endangered languages, community revitalization.